Polyvinyl alcohol / cellulose high-strength high-toughness spiral large-size long fiber and preparation method thereof
Through electrospinning and twisting technology, high-strength, high-strength, spiral-shaped large-size long fibers were prepared, which solved the problem of insufficient mechanical properties and toughness of materials in the prior art, and achieved efficient and low-cost fiber material preparation, which was suitable for multiple industry fields.
Patent Information
- Application Number
- CN202510007061.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for the existing technology to prepare high-strength and high-tough fiber materials on a large scale at low cost and efficient basis, especially in applications in the fields of textile industry, environmental protection and biomedicine, and the mechanical properties and toughness of existing materials are insufficient.
Cellulose nanowhiskers (CNCm) directionally reinforced polyvinyl alcohol (PVA) are prepared by electrospinning technology, and spiral, adjustable length and diameter high-strength and high-strength fibers are formed through twisting technology.
It significantly improves the tensile strength and toughness of the fiber, realizes the preparation of high-strength, high-strength, spiral, large-size long fibers. It is suitable for many industries and has the advantages of low cost, controllable process, simple and efficient operation.
Smart Images

Figure CN119800564A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber technology, and in particular to a polyvinyl alcohol / cellulose high-strength and high-toughness spiral large-size long fiber and a preparation method thereof. Background Art
[0002] High-strength and high-tenacity fiber composites are widely needed in the fields of textile industry, environmental protection and biomedicine. Carbon fibers made from petrochemical raw materials have excellent tensile strength (up to 2-8GPa), but low toughness (elongation at break less than 4%, fracture energy of 15-30kJ / m 2 ) (Ceramics International, 2023, 49(4):6451). Selecting suitable raw materials to prepare high-strength and high-tenacity fiber composites is of great practical significance. Spider silk is a natural high-strength and high-tenacity fiber with a tensile strength of more than 1.2 GPa and high toughness (elongation at break is 126%-750%, and fracture energy is 9.33-29.8 kJ / m 2 ) (Advanced science, 2021, 9(5): e2103965). However, it is currently impossible to obtain spider silk on a large scale through breeding methods, and the artificial synthesis of spider silk protein is very expensive. Therefore, how to quickly, efficiently and low-costly prepare high-strength and high-tenacity fiber materials on a large scale has become a problem that the industry needs to solve urgently.
[0003] Polyvinyl alcohol (PVA) is a water-soluble polymer with good film-forming properties and biocompatibility. After being prepared into films and gels, it is widely used in biomedicine, beauty technology, environmental protection and other fields. Yu Chuanli prepared PVA nanofiber membranes by electrospinning, with an elongation at break of 56.39%, showing excellent deformation ability, but its tensile strength is only 2.81MPa (Synthetic Fiber Industry, 2023, 46(01):15), and its mechanical properties are relatively weak, which cannot meet the requirements of high-strength composite fiber materials for mechanical properties and durability in industrial textiles, biomedicine and other fields.
[0004] Cellulose nanowhiskers (CNC) are nano-sized materials that can be extracted from natural plants through chemical, mechanical and biological processing methods. They have high crystallinity and specific surface area, and excellent mechanical properties (CNC tensile strength can reach 10GPa, and Young's modulus can reach 180GPa). When used as a reinforcing phase and composited with polymers, they can effectively improve the mechanical properties of the polymer matrix. Studies have been conducted to prepare PVA / CNC composite films using casting, with an elongation at break of 305.6%, but a tensile strength of only 33.91MPa (Modern Chemical Industry, 2024, 44(02):199). This is because the reinforcing phase CNC is randomly distributed in the polymer matrix and cannot effectively bear and transfer stress, resulting in poor reinforcement effect.
[0005] Electrospinning is an important way to prepare nanofibers. The collection device can adjust the distribution and orientation of nanofibers. It has the advantages of simple device, convenient molding, and controllable process. Twisting technology induces the fiber to twist around the axis through mechanical stress. The fibers embrace each other to form high-strength and high-tenacity spiral fibers with adjustable internal microstructure and macroscopic stress deformation. This invention proposes for the first time to use electrospinning technology to prepare cellulose nanowhiskers (CNC m ) Directionally reinforced polyvinyl alcohol (PVA) and PVA / CNC m The flexible membrane with oriented distribution of composite nanofibers improves the tensile strength and toughness of the membrane, and high-strength, high-toughness, spiral, large-size PVA / CNC is prepared by twisting m Long fibers can be used in the textile industry, environmental protection, biomedicine and other fields, and have important practical significance. Summary of the invention
[0006] The purpose of the present invention is to provide a polyvinyl alcohol / cellulose high-strength, high-toughness, spiral large-size long fiber and a preparation method thereof. The core of the present invention is (1) using an electrospinning process to achieve ① CNC m Directed distribution enhancement in PVA matrix, ②PVA / CNC m The orientation of composite nanofibers can be controlled and distributed to obtain PVA / CNC m (2) The flexible film is subjected to fiberization treatment by twisting process to obtain a spiral high-strength and high-tenacity fiber with adjustable length. This method has the advantages of low cost, controllable process, simple operation and high efficiency.
[0007] The technical solution of the present invention is achieved in this way:
[0008] The present invention provides a method for preparing high-strength and high-tenacity polyvinyl alcohol / cellulose spiral large-size long fibers, which is characterized by comprising the following steps:
[0009] S1. Modified cellulose nanowhisker CNC m Preparation: Modified cellulose nanowhiskers CNC with specific functional groups are prepared by acid hydrolysis and oxidation of natural plant fibers. m ;
[0010] S2. Electrospinning PVA / CNC m Preparation of composite nanofiber flexible membrane: The modified cellulose nanowhisker CNC m , polyvinyl alcohol PVA and deionized water to prepare PVA / CNC m Mix the solution, obtain composite nanofibers by electrospinning, and obtain PVA / CNC by deposition and bonding. mComposite nanofiber flexible membrane;
[0011] S3.PVA / CNC m Directional twisting of flexible film: PVA / CNC prepared in S2 m The composite nanofiber flexible film is cut into long strips, and the strips are subjected to directional mechanical twisting by manual twisting or mechanical twisting device to obtain PVA / CNC m Long fibers;
[0012] S4. Impregnation modification of polyvinyl alcohol / cellulose high-strength, high-toughness, spiral large-size long fibers: prepare a cross-linking modification solution, and impregnate and modify the PVA / CNC long fibers in S3 to obtain polyvinyl alcohol / cellulose high-strength, high-toughness, spiral large-size long fibers; the cross-linking modification solution is a 0.5wt%-5wt% cross-linking modification solution, and the cross-linking modification solution is selected from at least one of glutaraldehyde, citric acid, chitosan, silver ammonia, graphene oxide, and carbon nanotubes.
[0013] As a further improvement of the present invention, the specific functional group in step S1 is selected from at least one of an aldehyde group, a carboxyl group, and a sulfonic acid group; the modified cellulose nanowhisker CNC m The diameter is 8-25nm, the length is 100-900nm, the aspect ratio is 10-100, the degree of functional group substitution is 0.1-1.5, and the Zeta potential value is -33 to -53mV. The method for preparing modified nanocellulose includes sulfuric acid hydrolysis method, sodium periodate oxidation method, ammonium persulfate oxidation method, etc.
[0014] As a further improvement of the present invention, the PVA / CNC m The concentration of polyvinyl alcohol in the mixed solution is 7wt%-12wt%, CNC m The mass ratio to the PVA aqueous solution is 0.1-6:100.
[0015] As a further improvement of the present invention, the spinning voltage of the electrospinning in step S2 is 10-20 kV, the vertical distance between the spinneret and the collecting roller is 10-20 cm, the rotating speed of the collecting roller is 1000-2400 r / min, and the liquid discharge rate of the spinneret is 0.5-1.5 mL / h.
[0016] As a further improvement of the present invention, the modified cellulose nano whisker CNC m The orientation angle inside the composite nanofiber is 0°. m The orientation angle in the composite nanofiber flexible membrane is 0-80°.
[0017] As a further improvement of the present invention, the PVA / CNC mThe composite nanofiber flexible membrane has a width of 10-50 cm, a length of 50-200 cm, and a thickness of 0.01-0.05 cm. m In the composite nanofiber flexible film, the diameter of the composite nanofiber is 100-600nm, and the crystallinity of the polyvinyl alcohol nanofiber in the flexible film is 22%-40%.
[0018] As a further improvement of the present invention, the width of the strip in step S3 is 0.2-10 cm and the length is 10-200 cm; the twist of the twisting treatment is 0.2-3 t / cm, the twist angle is 10-80°, the twist coefficient is 4.0-5.5, and the diameter of the PVA / CNC long fiber obtained after twisting is 0.05-5 cm, the length is 5-160 cm, and the density is 1.0-1.6 g / cm 3 .
[0019] As a further improvement of the present invention, the impregnation modification in step S4 controls the impregnation temperature to be 20-60°C for 1-6 hours, and places the fiber in a 40°C oven for 24 hours or naturally air-dries at room temperature until the moisture content in the fiber is 5%-10%.
[0020] As a further improvement of the present invention, the natural plant fiber includes at least one of all seed fibers, stem bast fibers, leaf fibers, and fruit fibers. The natural plant fibers include all seed fibers (such as cotton fibers), stem bast fibers (such as wood, bamboo, and ramie fibers), leaf fibers (abaca fibers), and fruit fibers (coconut shell fibers).
[0021] The present invention further protects a polyvinyl alcohol / cellulose high-strength and high-tenacity, spiral large-size long fiber prepared by the above-mentioned preparation method, wherein the polyvinyl alcohol / cellulose high-strength and high-tenacity, spiral large-size long fiber has a tensile strength between 100-400MPa and an elongation at break between 150%-350%.
[0022] Preferably, the method specifically comprises the following steps:
[0023] (1) Extracting and preparing CNC with specific functional groups from natural plant fibers through acid hydrolysis and oxidation treatment m (Aldehyde CNC -CHO , carboxyl CNC -COOH , sulfonic acid CNC -SO3H ), including CNC m The diameter is 8-25nm, the length is 100-900nm, the aspect ratio is 10-100, the degree of functional group substitution is 0.1-1.5, and the Zeta potential value is -33 to -53mV.
[0024] (2) The CNC prepared in step S1 m , PVA and deionized water were prepared into different concentrations of PVA / CNC in a certain proportion. m Mix the solution and obtain CNC by electrospinning m Directional reinforcement PVA / CNC m The nanofibers are oriented and distributed in a flexible film. Among them, the PVA concentration is 7wt%-12wt%, CNC m The mass ratio of the spinning needle to the PVA aqueous solution is 0.1-6:100, the spinning voltage is 10-20 kV, the vertical distance between the spinning needle and the collecting roller is 10-20 cm, the collecting roller speed is 1000-2400 r / min, and the liquid discharge rate of the spinning needle is 0.5-1.5 mL / h; the prepared PVA / CNC m In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 100-600nm, CNC m The composite nanofibers are arranged in parallel at 0° inside the composite nanofibers, and are approximately distributed in parallel at 0-80° inside the flexible membrane.
[0025] (3) PVA / CNC prepared in S2 m The flexible film is cut into strips with a width of 0.2-5cm and a length of 10-200cm. The strips are subjected to directional mechanical twisting by a mechanical twisting device, wherein the twist is 0.2-3t / cm, the twist angle is 10-80°, and the twist coefficient is 4.0-5.5. The high-strength and high-toughness spiral PVA / CNC obtained after twisting m The long fiber diameter is 0.05-5cm, the length is 5-160cm, and the density is 1.2-1.6g / cm 3 .
[0026] (4) Prepare 0.5wt%-5wt% glutaraldehyde or citric acid, chitosan or silver ammonia, graphene oxide or carbon nanotube solution to treat PVA / CNC in S3 m The long fiber is impregnated and modified, the impregnation temperature is controlled to be 20-60°C, the time is 1-6 hours, and it is placed in a 40°C oven for 24 hours or naturally air-dried at room temperature until the moisture content in the fiber is 5%-10%.
[0027] The present invention has the following beneficial effects: the present invention firstly adopts modified cellulose nano whiskers (CNC) with high charge density m ) as a reinforcing material for polyvinyl alcohol (PVA) polymer molecules, it not only forms a stable hydrogen bond with the PVA molecular chain, but also effectively improves the load transfer capacity of the PVA matrix; secondly, by precisely controlling the electrospinning process, CNC m Directed distribution enhancement in PVA matrix, PVA / CNC mThe orientation of composite nanofibers can be controlled and distributed to obtain PVA / CNC m The flexible film with oriented distribution of composite nanofibers; finally, the flexible film is subjected to fiberization treatment by twisting process, so as to obtain a spiral high-strength and high-tenacity fiber with adjustable length. The method adopted by the present invention has low cost, controllable process, simple and efficient operation, can realize large-scale industrial production, and provides an efficient and low-cost solution for the development of high-performance, green and degradable fiber material preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0029] Figure 1 This is a flow chart for producing high-strength, high-toughness, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose of the present invention;
[0030] Figure 2 Transmission electron microscopy images of two different nanocellulose whiskers prepared in Example 1 of the present invention (A. cellulose nanowhiskers (CNC); B. sulfonate cellulose nanowhiskers (CNC -SO3H ));
[0031] Figure 3 Preparation of PVA / CNC by electrospinning in Example 1 of the present invention -SO3H Composite nanofiber flexible membrane (A. electrospun PVA / CNC -SO3H Schematic diagram of the flexible membrane preparation process; B. Electrospinning PVA / CNC -SO3H SEM image of flexible membrane fiber);
[0032] Figure 4 The PVA fiber flexible membrane prepared by electrospinning in Comparative Example 1 of the present invention (A. Schematic diagram of the preparation process of the electrospinning PVA fiber flexible membrane; B. Scanning electron microscope image of the electrospinning PVA fiber flexible membrane);
[0033] Figure 5 The PVA / CNC prepared by directional twisting in Example 1 of the present invention -SO3H Helical long fibers (A. PVA / CNC prepared by twisting -SO3H Schematic diagram of the spiral long fiber process; B. PVA / CNC produced by twisting -SO3H Actual picture of spiral long fiber; C. Preparation of PVA / CNC by twisting -SO3H (Scanning electron microscope image of the microstructure of spiral long fibers). DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] like Figure 1 This embodiment provides a method for preparing high-strength and high-tenacity, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose, comprising the following steps:
[0037] S1. Using eucalyptus fiber as raw material, cellulose nanowhiskers (CNC) and sulfonic acid cellulose nanowhiskers (CNC) were prepared by mechanical grinding combined with ultrasonic crushing and sulfuric acid hydrolysis. -SO3H ), the CNC diameter was 8-25nm, the length was 100-900nm, the aspect ratio was 10-100, and the surface Zeta potential value was -33 to -35mV, while CNC -SO3H The diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of the sulfonic acid functional group is 0.5-0.6, and the surface Zeta potential value is -35 to -46mV; Figure 2 CNC and CNC in -SO3H The transmission electron microscopy image shows that cellulose sulfonate nanowhiskers (CNC -SO3H ) has more uniform shape and size and good dispersion.
[0038] S2. Set the CNC in S1 -SO3H , PVA and deionized water to prepare PVA / CNC -SO3H Mixed solution, the quality of which is higher than CNC -SO3H :PVA:H2O is 0.5:12:87.5, PVA / CNC -SO3H The mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 10 kV, the vertical distance between the spinneret and the collecting roller was 10 cm, the collecting roller speed was 1000 r / min, and the liquid discharge rate of the spinneret was 0.5 mL / h. -SO3H In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 400-550nm, CNC -SO3H They are distributed in 0° parallel arrangement inside the composite nanofibers; Figure 3 Preparation of PVA / CNC by electrospinning in Example 1 -SO3HComposite nanofiber flexible membrane, PVA / CNC can be seen -SO3H The composite fibers are distributed in the flexible membrane at an orientation of 80° with respect to the length direction of the membrane.
[0039] S3. Prepare PVA / CNC in S2 -SO3H The flexible film is cut into strips with a width of 0.2 cm and a length of 10 cm. The strips are subjected to directional mechanical twisting by a mechanical twisting device, wherein the twist is 0.2 t / cm, the twist angle is 55°, and the twist coefficient is 4.0. The high-strength and high-toughness spiral PVA / CNC obtained after twisting -SO3H The long fiber diameter is 0.05cm, the length is 5cm, and the density is 1.2g / cm 3 ; Figure 5 The PVA / CNC prepared by directional twisting in Example 1 -SO3H Spiral long fibers, PVA / CNC can be seen -SO3H The composite nanofibers are oriented at 60° along the length direction of the helical fibers.
[0040] S4. Prepare 0.5% glutaraldehyde solution for PVA / CNC in S3 -SO3H The long fiber is impregnated and modified. The impregnation temperature is controlled to be 20°C, the reaction time is 1 hour, and it is placed in a 40°C oven for 24 hours until the moisture content in the fiber is 5%-10%.
[0041] Example 2
[0042] like Figure 1 This embodiment provides a method for preparing high-strength and high-tenacity, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose, comprising the following steps:
[0043] S1.Using eucalyptus fiber as raw material, sulfonated cellulose nanowhiskers (CNC -SO3H ), measured CNC -SO3H The diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of functional groups is 0.6-0.8, and the surface Zeta potential value is -35 to -46mV;
[0044] S2. Set the CNC in S1 -SO3H , PVA and deionized water to prepare PVA / CNC -SO3H Mixed solution, the quality of which is higher than CNC -SO3H :PVA:H2O is 1:11:88, PVA / CNC -SO3HThe mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 12 kV, the vertical distance between the spinneret and the collecting roller was 12 cm, the collecting roller speed was 1300 r / min, and the liquid discharge rate of the spinneret was 0.7 mL / h. -SO3H In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 350-500nm, CNC -SO3H The composite nanofibers are distributed in parallel arrangement at 0° inside the composite nanofibers, and the composite nanofibers are distributed in an orientation of 60° to the length direction of the membrane inside the flexible membrane;
[0045] S3. Prepare PVA / CNC in S2 -SO3H The flexible film is cut into strips with a width of 2 cm and a length of 20 cm. The strips are subjected to directional mechanical twisting by a mechanical twisting device. The twist is 1t / cm, the twist angle is 60°, and the twist coefficient is 4.3. The high-strength and high-toughness spiral PVA / CNC obtained after twisting -SO3H The long fiber diameter is 1 cm, the length is 16 cm, and the density is 1.3 g / cm 3 ;
[0046] S4. Prepare 1% citric acid solution for PVA / CNC in S3 -SO3H The long fiber is impregnated and modified. The impregnation temperature is controlled to be 25°C, the reaction time is 2 hours, and it is placed in a 40°C oven for 24 hours until the moisture content in the fiber is 5%-10%.
[0047] Example 3
[0048] like Figure 1 This embodiment provides a method for preparing high-strength and high-tenacity, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose, comprising the following steps:
[0049] S1. Using bamboo fiber as raw material, sodium periodate oxidation method was used to prepare aldehyde-based cellulose nanowhiskers (CNC -CHO ), measured CNC -CHO The diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of functional groups is 0.2-0.8, and the surface Zeta potential value is -37 to -40mV;
[0050] S2. Set the CNC in S1 -CHO , PVA and deionized water to prepare PVA / CNC -CHO Mixed solution, the quality of which is higher than CNC -CHO :PVA:H2O is 3:10:87, PVA / CNC -CHOThe mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 14 kV, the vertical distance between the spinneret and the collecting roller was 14 cm, the collecting roller speed was 1600 r / min, and the liquid discharge rate of the spinneret was 0.9 mL / h. -CHO In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 300-450nm, CNC -CHO The composite nanofibers are distributed in parallel arrangement at 0° inside the composite nanofibers, and the composite nanofibers are distributed in an orientation of 50° with respect to the length direction of the membrane inside the flexible membrane;
[0051] S3. Prepare PVA / CNC in S2 -CHO The flexible film is cut into strips with a width of 3 cm and a length of 80 cm. The strips are subjected to directional mechanical twisting by a mechanical twisting device. The twist is 1.5 t / cm, the twist angle is 65°, and the twist coefficient is 4.6. The high-strength and high-toughness spiral PVA / CNC obtained after twisting -CHO The long fiber diameter is 1.5cm, the length is 60cm, and the density is 1.4g / cm 3 ;
[0052] S4. Preparation of 2% chitosan solution for PVA / CNC in S3 -CHO The long fiber is impregnated and modified. The impregnation temperature is controlled to be 30°C, the reaction time is 1 hour, and it is placed in a 40°C oven for 24 hours until the moisture content in the fiber is 5%-10%.
[0053] Example 4
[0054] like Figure 1 This embodiment provides a method for preparing high-strength and high-tenacity, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose, comprising the following steps:
[0055] S1. Using bamboo fiber as raw material, sodium periodate oxidation method was used to prepare aldehyde-based cellulose nanowhiskers (CNC -CHO ), measured CNC -CHO The diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of functional groups is 0.7-0.8, and the surface Zeta potential value is -37 to -40mV;
[0056] S2. Set the CNC in S1 -CHO , PVA and deionized water to prepare PVA / CNC -CHO Mixed solution, the quality of which is higher than CNC -CHO :PVA:H2O is 5:9:86, PVA / CNC -CHOThe mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 16 kV, the vertical distance between the spinneret and the collecting roller was 16 cm, the collecting roller speed was 1900 r / min, and the liquid discharge rate of the spinneret was 1.1 mL / h. -CHO In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 250-400nm, CNC -CHO The composite nanofibers are distributed in parallel arrangement at 0° inside the composite nanofibers, and the composite nanofibers are distributed in an orientation of 30° with respect to the length direction of the membrane inside the flexible membrane;
[0057] S3. Prepare PVA / CNC in S2 -CHO The flexible film is cut into strips with a width of 5 cm and a length of 130 cm. The strips are subjected to directional mechanical twisting by a mechanical twisting device, wherein the twist degree is 2t / cm, the twist angle is 70°, and the twist coefficient is 5. The high-strength and high-tenacity spiral PVA / CNC obtained after twisting -CHO The long fiber diameter is 2.5cm, the length is 115cm, and the density is 1.5g / cm 3 ;
[0058] S4. Prepare 3% silver ammonia solution for PVA / CNC in S3 -CHO The long fiber is impregnated and modified. The impregnation temperature is controlled to be 40°C, the reaction time is 4 hours, and it is placed in a 40°C oven for 24 hours until the moisture content in the fiber is 5%-10%.
[0059] Example 5
[0060] like Figure 1 This embodiment provides a method for preparing high-strength and high-tenacity, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose, comprising the following steps:
[0061] S1. Using straw fiber as raw material, carboxycellulose nanowhiskers (CNC -COOH ), measured CNC -COOH The diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of functional groups is 0.9-1.0, and the surface Zeta potential value is -39 to -53mV;
[0062] S2. Set the CNC in S1 -COOH , PVA and deionized water to prepare PVA / CNC -COOH Mixed solution, the quality of which is higher than CNC -COOH :PVA:H2O is 8:8:84, PVA / CNC -COOHThe mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 18 kV, the vertical distance between the spinneret and the collecting roller was 18 cm, the collecting roller speed was 2100 r / min, and the liquid discharge rate of the spinneret was 1.3 mL / h. -COOH In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 200-350nm, CNC -COOH The composite nanofibers are distributed in parallel arrangement at 0° inside the composite nanofibers, and the composite nanofibers are distributed in an orientation of 20° with respect to the length direction of the membrane inside the flexible membrane;
[0063] S3. Prepare PVA / CNC in S2 -COOH The flexible film is cut into strips with a width of 7 cm and a length of 160 cm. The strips are subjected to directional mechanical twisting by a mechanical twisting device. The twist is 2.5 t / cm, the twist angle is 75°, and the twist coefficient is 5.2. The high-strength and high-toughness spiral PVA / CNC obtained after twisting -COOH The long fiber diameter is 3.5cm, the length is 140cm, and the density is 1.6g / cm 3 ;
[0064] S4. Preparation of 4% graphene oxide solution for PVA / CNC in S3 -COOH The long fiber was impregnated and modified. The impregnation temperature was controlled to be 50°C, the reaction time was 5 hours, and it was placed in a 40°C oven for 24 hours until the moisture content in the fiber was 5%-10%.
[0065] Example 6
[0066] like Figure 1 This embodiment provides a method for preparing high-strength and high-tenacity, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose, comprising the following steps:
[0067] S1. Using straw fiber as raw material, carboxycellulose nanowhiskers (CNC -COOH ), measured CNC -COOH The diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of functional groups is 1.3-1.5, and the surface Zeta potential value is -39 to -53mV;
[0068] S2. Set the CNC in S1 -COOH , PVA and deionized water to prepare PVA / CNC -COOH Mixed solution, the quality of which is higher than CNC -COOH :PVA:H2O is 10:7:83, PVA / CNC -COOHThe mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 20 kV, the vertical distance between the spinneret and the collecting roller was 20 cm, the collecting roller speed was 2400 r / min, and the liquid discharge rate of the spinneret was 1.5 mL / h. m In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 150-300nm, CNC -COOH The composite nanofibers are distributed in parallel arrangement at 0° inside the composite nanofibers, and the composite nanofibers are distributed in an orientation of 5° with respect to the length direction of the membrane inside the flexible membrane;
[0069] S3. Prepare PVA / CNC in S2 -COOH The flexible film is cut into strips with a width of 10 cm and a length of 200 cm. The strips are subjected to directional mechanical twisting by a mechanical twisting device. The twist is 3t / cm, the twist angle is 80°, and the twist coefficient is 5.5. The high-strength and high-toughness spiral PVA / CNC obtained after twisting -COOH The long fiber diameter is 5cm, the length is 160cm, and the density is 1.6g / cm 3 ;
[0070] S4. Prepare 5% carbon nanotube solution for PVA / CNC in S3 -COOH The long fiber is impregnated and modified. The impregnation temperature is controlled to be 60°C, the reaction time is 6 hours, and it is placed in a 40°C oven for 24 hours until the moisture content in the fiber is 5%-10%.
[0071] Comparative Example 1 Preparation of PVA nanofiber membrane (non-oriented fibers)
[0072] The following steps are involved:
[0073] PVA and deionized water were prepared into a PVA solution, wherein the mass ratio of PVA:H2O was 8:92. The PVA mixed solution was dispersed by ultra-high-speed stirring and then transferred to an electrospinning machine. The spinning voltage was set to 18kV, the vertical distance between the spinneret and the collecting roller was 18cm, the collecting roller speed was 600r / min, and the spinneret liquid discharge rate was 1.3mL / h. In the prepared PVA nanofiber flexible membrane, the diameter of the nanofibers was 200-350nm. Figure 4 It can be seen that the PVA fibers are randomly oriented and distributed in the flexible film.
[0074] Comparative Example 2 Preparation of PVA Nanofiber Membrane (Fiber Orientation)
[0075] The following steps are involved:
[0076] PVA and deionized water were prepared into a PVA solution with a mass ratio of PVA:H2O of 8:92. The PVA mixed solution was transferred to an electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 18 kV, the vertical distance between the spinneret and the collecting roller was 18 cm, the collecting roller speed was 2100 r / min, and the liquid discharge rate of the spinneret was 1.3 mL / h. In the prepared PVA nanofiber flexible membrane, the diameter of the nanofibers was 200-350 nm, and the fibers were distributed approximately parallel at 10° in the flexible membrane.
[0077] Comparative Example 3 PVA / CNC 1% Preparation of composite nanofiber flexible membrane (without fiber orientation)
[0078] The following steps are involved:
[0079] S1. Using straw fiber as raw material, carboxycellulose nanowhiskers (CNC -COOH ), measured CNC -COOH The diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of functional groups is 0.3-1.0, and the surface Zeta potential value is -39 to -53mV;
[0080] S2. Set the CNC in S1 -COOH , PVA and deionized water to prepare PVA / CNC -COOH Mixed solution, the quality of which is higher than CNC -COOH :PVA:H2O is 8:8:84, PVA / CNC -COOH The mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 18 kV, the vertical distance between the spinneret and the collecting roller was 18 cm, the collecting roller speed was 600 r / min, and the liquid discharge rate of the spinneret was 1.3 mL / h. -COOH In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 200-350nm, CNC -COOH The composite nanofibers are arranged in parallel at 0° inside and randomly distributed in the flexible membrane.
[0081] Comparative Example 4 PVA / CNC 8% Preparation of composite nanofiber flexible membrane (fiber orientation)
[0082] The following steps are involved:
[0083] S1. Using straw fiber as raw material, carboxycellulose nanowhiskers (CNC -COOH ), measured CNC -COOHThe diameter is 4-10nm, the length is 100-200nm, the aspect ratio is 10-50, the degree of substitution of functional groups is 0.3-1.0, and the surface Zeta potential value is -39 to -53mV;
[0084] S2. Set the CNC in S1 -COOH , PVA and deionized water to prepare PVA / CNC -COOH Mixed solution, the quality of which is higher than CNC -COOH :PVA:H2O is 8:8:84, PVA / CNC -COOH The mixed solution was transferred to the electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 18 kV, the vertical distance between the spinneret and the collecting roller was 18 cm, the collecting roller speed was 2100 r / min, and the liquid discharge rate of the spinneret was 1.3 mL / h. -COOH In the composite nanofiber flexible membrane, the diameter of the composite nanofiber is 100-600nm, CNC -COOH The composite nanofibers are arranged parallel to each other at 0° inside the composite nanofibers, and are approximately parallel to each other at 10° inside the flexible membrane.
[0085] Comparative Example 5 Preparation of PVA spiral long fibers (non-oriented fibers)
[0086] The following steps are involved:
[0087] S1. PVA and deionized water were prepared into a PVA solution, wherein the mass ratio of PVA:H2O was 8:92, and the PVA mixed solution was transferred to an electrospinning machine after ultra-high-speed stirring and dispersion, and the spinning voltage was set to 18 kV, the vertical distance between the spinneret and the collecting roller was 18 cm, the collecting roller speed was 600 r / min, and the liquid discharge rate of the spinneret was 1.3 mL / h; in the prepared PVA nanofiber flexible film, the diameter of the nanofibers was 200-350 nm, and the nanofibers were randomly distributed in the flexible film;
[0088] S2. The PVA nanofiber flexible film prepared in S1 was cut into strips with a width of 7 cm and a length of 160 cm. The PVA nanofiber flexible film strips were subjected to directional mechanical twisting by a mechanical twisting device, wherein the twist was 2.5 t / cm, the twist angle was 75°, and the twist coefficient was 5.2. The spiral PVA long fibers obtained after twisting had a diameter of 3.5 cm, a length of 140 cm, and a density of 1.6 g / cm 3 ;
[0089] S3. Prepare 4% graphene oxide solution to impregnate the PVA long fibers in S2. Control the impregnation temperature to 50° C., the time to 5 hours, and place in a 40° C. oven for 24 hours until the moisture content in the fibers is 5%-10%.
[0090] Comparative Example 6 Preparation of PVA spiral long fibers (fiber orientation)
[0091] The following steps are involved:
[0092] S1. PVA and deionized water were prepared into a PVA solution, wherein the mass ratio of PVA:H2O was 8:92. The PVA mixed solution was transferred to an electrospinning machine after ultra-high-speed stirring and dispersion. The spinning voltage was set to 18 kV, the vertical distance between the spinneret and the collecting roller was 18 cm, the collecting roller speed was 2100 r / min, and the liquid discharge rate of the spinneret was 1.3 mL / h. In the prepared PVA nanofiber flexible membrane, the diameter of the nanofibers was 200-350 nm, and the nanofibers were distributed approximately parallel at 10° in the flexible membrane.
[0093] S2. The PVA nanofiber flexible film prepared in S1 was cut into strips with a width of 7 cm and a length of 160 cm. The PVA nanofiber flexible film strips were subjected to directional mechanical twisting by a mechanical twisting device, wherein the twist was 2.5 t / cm, the twist angle was 75°, and the twist coefficient was 5.2. The spiral PVA long fibers obtained after twisting had a diameter of 3.5 cm, a length of 140 cm, and a density of 1.6 g / cm 3 ;
[0094] S3. Prepare a 4% graphene oxide solution to impregnate the PVA long fibers in S2. Control the impregnation temperature to 50° C., the time to 5 hours, and place in a 40° C. oven for 24 hours until the moisture content in the fibers is 5%-10%.
[0095] Test Example 1
[0096] The cellulose nano whiskers (CNC) and modified cellulose nano whiskers (CNC) prepared in Examples 1-6 of the present invention are m ) was used to test the surface Zeta potential value, and the results are shown in Table 1.
[0097] The test method is as follows: by measuring the migration velocity of particles in the nanocellulose whisker suspension and the conductivity in the liquid phase and other parameters, the surface Zeta potential value of the nanocellulose whisker is calculated.
[0098] Table 1 Surface Zeta potential values of cellulose nanowhiskers and modified cellulose nanowhiskers
[0099] sample Zeta potential (mV) CNC (Example 1) -30 to -35 <![CDATA[CNC -SO3H (Examples 1 and 2)]]> -35 to -46 <![CDATA[CNC -CHO (Examples 3 and 4)]]> -37 to -40 <![CDATA[CNC -COOH (Examples 5 and 6)]]> -39 to -53
[0100] As shown in Table 1, nanocellulose (CNC) has a large number of hydroxyl groups (-OH) in its molecular structure, which will be ionized in aqueous solution to form negative charges and thus show electronegativity, usually . The present invention chemically modifies the hydroxyl groups of nanocellulose whiskers and introduces negatively charged functional groups such as carboxyl (-COOH), sulfonic acid (-SO3H) and aldehyde (-CHO), which will significantly improve the modified nanocellulose (CNC) m ) surface charge density, resulting in the modified nanocellulose (CNC m )’s surface Zeta potential value decreases, which can improve its dispersibility and interface bonding strength in PVA solution.
[0101] Test Example 2
[0102] Mechanical properties of the nanofiber flexible membranes and spiral long fibers prepared in Examples 1-6 of the present invention and Comparative Examples 1-6 were tested. The results are shown in Tables 2 and 3.
[0103] The test method is as follows: Referring to the national standards GB / T 14344-2022 and GB / T 1447-2005, the tensile properties of the nanofiber flexible membrane and the spiral long fiber were tested respectively on a desktop electronic universal material testing machine.
[0104] Table 2 Tensile performance test of nanofiber flexible membrane and spiral long fiber in comparative example
[0105]
[0106] As shown in Table 2, in Comparative Example 1, the non-oriented PVA nanofiber membrane prepared by the electrospinning process has a maximum tensile elongation at break of 400%, but the crystallinity and tensile strength are low, only 20% and 10MPa. In Comparative Example 3, the present invention uses electrospinning technology to realize the orientation distribution of CNCm-oriented reinforced PVA and PVA / CNCm composite nanofibers in the flexible membrane, which can significantly improve its crystallinity and tensile strength, but the elongation at break is still maintained at about 300%, and the deformation is large. By introducing nanocellulose as a reinforcing phase in PVA, a large number of intermolecular hydrogen bonds are formed between the large number of hydroxyl groups on the surface of nanocellulose and the hydroxyl groups on the PVA molecular chain, which promotes the molecular crystallization of PVA, and improves the mechanical properties of the composite nanofiber flexible membrane by stress transfer. In Comparative Example 6, after the present invention twists the flexible membrane into a spiral fiber, the tensile strength and tensile deformation are significantly increased due to the enhancement of the interaction between the fibers, the untwisting to enhance the tensile deformation, and the strengthening of the structural stability.
[0107] Table 3 Helical PVA / CNC in the examples m Long fiber tensile properties test
[0108]
[0109] As can be seen from Table 3, the present invention uses twisting technology to transform a flexible membrane with an oriented distribution of nanofibers in the membrane into a spiral long fiber, and can obtain large-sized long fibers with high strength and toughness by reducing defects through large-scale volume shrinkage, enhancing the bonding effect between oriented nanofibers, dissipating and absorbing energy during the unwinding process, and dissipating energy through multi-scale deformation under stress loads.
[0110] Test Example 3
[0111] The water resistance of the PVA / CNC spiral long fibers (modified by impregnation with glutaraldehyde or citric acid solution) prepared in Examples 1 and 2 was evaluated using a universal material testing machine, and the wet tensile strength was found to be 150-180 MPa, which was only 10 MPa lower than the dry tensile strength.
[0112] According to the WS / T 650-2019 "Antibacterial and Antibacterial Effect Evaluation Method" standard, the antibacterial rate of the PVA / CNC spiral long fibers (modified by impregnation with chitosan or silver ammonia solution) prepared in Examples 3 and 4 was evaluated, and the antibacterial rate against Staphylococcus aureus and Escherichia coli was measured to be more than 99%.
[0113] The conductivity of the PVA / CNC spiral long fibers (modified by impregnation with graphene oxide or carbon nanotube solution) prepared in Examples 5 and 6 was evaluated using a four-wire resistance tester, and the conductivity was measured to be 0.12 S / m±0.01 S / m.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing high-strength and high-tenacity, spiral large-size long fibers of polyvinyl alcohol / cellulose, characterized in that: The following steps are involved: S1. Modified cellulose nanowhisker CNC m Preparation: Modified cellulose nanowhiskers CNC with specific functional groups are prepared by acid hydrolysis and oxidation of natural plant fibers. m ; S2. Electrospinning PVA / CNC m Preparation of composite nanofiber flexible membrane: The modified cellulose nanowhiskers CNC m , polyvinyl alcohol PVA and deionized water to prepare PVA / CNC m Mix the solution, obtain composite nanofibers by electrospinning, and obtain PVA / CNC by deposition and bonding. m Composite nanofiber flexible membrane; S3.PVA / CNC m Directional twisting of flexible film: PVA / CNC prepared in S2 m The composite nanofiber flexible film is cut into long strips, and the strips are subjected to directional mechanical twisting by manual twisting or mechanical twisting device to obtain PVA / CNC m Long fibers; S4. Impregnation modification of high-strength, high-toughness, spiral-shaped, large-size long fibers of polyvinyl alcohol / cellulose: Prepare a cross-linking modification solution to impregnate the PVA / CNC in S3 m The long fibers are impregnated and modified to obtain high-strength and high-toughness, spiral large-size long fibers of polyvinyl alcohol / cellulose; the cross-linking modification solution is a 0.5wt%-5wt% cross-linking modification solution, and the cross-linking modification solution is selected from at least one of glutaraldehyde, citric acid, chitosan, silver ammonia, graphene oxide, and carbon nanotubes.
2. The preparation method according to claim 1, characterized in that: The specific functional group in step S1 is selected from at least one of an aldehyde group, a carboxyl group, and a sulfonic acid group; the modified cellulose nanowhisker CNC m The diameter is 8-25nm, the length is 100-900nm, the aspect ratio is 10-100, the degree of functional group substitution is 0.1-1.5, and the Zeta potential value is -33 to -53mV.
3. The preparation method according to claim 1, characterized in that: PVA / CNC in step S2 m The PVA concentration in the mixed solution is 7wt%-12wt%, CNC m The mass ratio to the PVA aqueous solution is 0.1-6:
100.
4. The preparation method according to claim 1, characterized in that: The spinning voltage of the electrospinning in step S2 is 10-20 kV, the vertical distance between the spinneret and the collecting roller is 10-20 cm, the rotating speed of the collecting roller is 1000-2400 r / min, and the liquid discharge rate of the spinneret is 0.5-1.5 mL / h.
5. The preparation method according to claim 1, characterized in that: The modified cellulose nanowhisker CNC m The orientation angle inside the composite nanofiber is 0°. m The orientation angle in the composite nanofiber flexible film is 0-70°.
6. The preparation method according to claim 1, characterized in that: PVA / CNC in step S2 m The composite nanofiber flexible membrane has a width of 10-50 cm, a length of 50-200 cm, and a thickness of 0.01-0.05 cm. m In the composite nanofiber flexible film, the diameter of the composite nanofiber is 100-600nm, and the crystallinity of the polyvinyl alcohol nanofiber in the flexible film is 22%-40%.
7. The preparation method according to claim 1, characterized in that: The width of the strip in step S3 is 0.2-10 cm and the length is 10-200 cm; the twist of the twisting treatment is 0.2-3 t / cm, the twist angle is 10-80°, the twist coefficient is 4.0-5.5, and the diameter of the PVA / CNC long fiber obtained after twisting is 0.05-5 cm, the length is 5-160 cm, and the density is 1.0-1.6 g / cm 3 .
8. The preparation method according to claim 1, characterized in that: The impregnation modification in step S4 is controlled by an impregnation temperature of 20-60° C. for 1-6 hours, and the fiber is placed in a 40° C. oven for 24 hours or naturally air-dried at room temperature until the moisture content in the fiber is 5%-10%.
9. The preparation method according to claim 1, characterized in that: The natural plant fiber includes at least one of seed fiber, stem bast fiber, leaf fiber and fruit fiber. Natural plant fibers include all seed fibers (such as cotton fibers), stem bast fibers (such as wood, bamboo, ramie fibers), leaf fibers (abaca fibers), and fruit fibers (coconut shell fibers).
10. A polyvinyl alcohol / cellulose high-strength, high-tenacity, spiral large-size long fiber obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The tensile strength of the polyvinyl alcohol / cellulose high-strength and high-tenacity spiral large-size long fibers is between 100-400 MPa, and the elongation at break is between 100%-350%.
Citation Information
Patent Citations
Method for manufacturing cellulose base heat-resisting nano-composite fiber membrane in electrostatic spinning mode
CN104928849A
Absorbent articles having nonwoven substrates with reactive ink compositions
CN107405236A
Preparation method of stretchable sensor
CN113143258A
Preparation method and application of elastic fiber
CN115110189A
High-strength cellulose nanocrystalline film and preparation method thereof
CN117229543A